2009
DOI: 10.6090/jarq.43.55
|View full text |Cite
|
Sign up to set email alerts
|

Flood Event Loadings of Nitrogen and Phosphorus from the Yahagi River to Chita Bay, Japan

Abstract: A 4-year data set of continuous monitoring of suspended matter and nutrients concentration has been analyzed to evaluate the inter-annual variability and the effects of flood events on the sediment transport and nitrogen, phosphorus loadings from the Yahagi River to Chita Bay, Japan. Nitrogen was mainly loaded in dissolved form, which accounted for 59% to 88% of the annual loads, while phosphorus was mainly loaded in particulate form (45% to 78%). Loads of suspended matter and total phosphorus (T-P) by the his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…Similarly, Yamada et al (2005) revealed that the DP was the largest portion of TP in Umeda River. The post-typhoon concentrations of DP suggest that P loading from land is mainly a function of erosion during flood events, a conclusion already reported for several major rivers in Japan (Tanaka et al, 2009). The pre-typhoon bottom water concentrations of DP, along the Toyo River and Umeda River transects, ranged from 0.031 − 0.062 mg/L and 0.024 − 0.088 mg/L, respectively (Fig.…”
Section: Nitrogen Response Induced By Typhoon No 14supporting
confidence: 74%
“…Similarly, Yamada et al (2005) revealed that the DP was the largest portion of TP in Umeda River. The post-typhoon concentrations of DP suggest that P loading from land is mainly a function of erosion during flood events, a conclusion already reported for several major rivers in Japan (Tanaka et al, 2009). The pre-typhoon bottom water concentrations of DP, along the Toyo River and Umeda River transects, ranged from 0.031 − 0.062 mg/L and 0.024 − 0.088 mg/L, respectively (Fig.…”
Section: Nitrogen Response Induced By Typhoon No 14supporting
confidence: 74%
“…Flood events can result in increased concentrations of inorganic cations (e.g., NH 4 + ) and organic acids (e.g., humic acid) in water. , These elevated concentrations have the potential to affect uptake on SDB-RPS sorbent (which has a mixed-mode weak cation exchange mechanism) by competing with herbicides for adsorption sites. In this context, further investigation on sorption mechanisms would be useful; however, it is still worthwhile to note the usefulness of laboratory derived R S applied in this work despite possible competition effects on uptake.…”
Section: Resultsmentioning
confidence: 99%
“…Flood events can result in increased concentrations of inorganic cations (e.g., NH 4 + ) 47 and organic acids (e.g., humic acid) in water. 48,49 These elevated concentrations have the potential to affect uptake on SDB-RPS sorbent (which has a mixed-mode weak cation exchange mechanism) by competing with herbicides for adsorption sites.…”
Section: Environmental Science and Technologymentioning
confidence: 99%